Halal Awareness: Mediation of Religious Beliefs and Halal Certification in Choosing Halal Food Through An Online Food Delivery Application - Helti Nur Aisyiah; Septi Kurnia Prastiwi; Asep Maulana Rohimat (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2023)
The prevalence of online food delivery applications for purchasing food has surged, especially in the wake of the COVID-19 pandemic. Various factors play a role in influencing food choices among buyers, with religious beliefs, halal certification, and halal awareness being significant contributors. This research focuses on examining the impact of these three variables on the food choices of Muslim millennials in Soloraya who also serve as respondents in this study. The independent variables are religious belief and halal certification, while halal awareness functions as a mediating variable, and halal food purchasing serves as the dependent variable. Employing a quantitative approach and utilizing the AMOS application for data processing, the study reveals that religious belief does not affect halal food purchasing, halal certification positively influences such choices, and halal awareness does not mediate the impact of religious belief and halal certification on halal food purchasing. The findings contribute to online food delivery service providers by encouraging the inclusion of halal information in their applications, prompting halal certification organizations to enhance socialization efforts regarding the significance of certification, and urging the public to elevate religious belief and halal awareness.